2015
DOI: 10.1210/en.2015-1143
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin Effect on Human β-Cells Mass and Function

Abstract: The osteoblast-specific hormone osteocalcin (OC) was found to regulate glucose metabolism, fat mass, and β-cell proliferation in mice. Here, we investigate the effect of decarboxylated OC (D-OC) on human β-cell function and mass in culture and in vivo using a Nonobese diabetic-severe combined immunodeficiency mouse model. We found that D-OC at dose ranges from 1.0 to 15 ng/mL significantly augmented insulin content and enhanced human β-cell proliferation of cultured human islets. This was paralleled by increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 53 publications
4
62
0
4
Order By: Relevance
“…Hence, the vast majority of OCN secreted by osteoblasts is trapped in bone ECM, in which it constitutes the most abundant noncollagenous polypeptide. Although both γ-carboxylated (Gla) and undercarboxylated (ucOCN) forms of OCN are detected in serum, most in vitro and in vivo studies concur to indicate that the endocrine function of OCN is fulfilled by ucOCN in mice and humans (3,4,11). This has been recently confirmed genetically through the inactivation of Ggcx specifically in osteoblasts, which resulted in increased circulating levels of ucOCN and improved glucose tolerance in mice (12).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hence, the vast majority of OCN secreted by osteoblasts is trapped in bone ECM, in which it constitutes the most abundant noncollagenous polypeptide. Although both γ-carboxylated (Gla) and undercarboxylated (ucOCN) forms of OCN are detected in serum, most in vitro and in vivo studies concur to indicate that the endocrine function of OCN is fulfilled by ucOCN in mice and humans (3,4,11). This has been recently confirmed genetically through the inactivation of Ggcx specifically in osteoblasts, which resulted in increased circulating levels of ucOCN and improved glucose tolerance in mice (12).…”
Section: Introductionmentioning
confidence: 97%
“…Accordingly, when fed a normal diet, Ocn-deficient mice (Ocn -/-) exhibit reduced glucose tolerance, insulin sensitivity, and circulating insulin levels, as well as decreased energy expenditure and increased fat mass (2). Mechanistic studies conducted in cell cultures and mice showed that OCN improves glucose handling by promoting insulin secretion from β cells (3,4), by favoring glucose uptake in myofibers (5), and by increasing energy expenditure (6). Studies in mice demonstrated that OCN function in β cells and myofibers is mediated through its binding to the G protein-coupled receptor family C group 6 member A (GPRC6A) (3,5).…”
Section: Introductionmentioning
confidence: 99%
“…Although energy metabolism is certainly a critical aspect of osteocalcin biology, whereby it affects 2 in mice, rats and humans 3-12 , functions of β-cells 13 , myoblasts and likely other cell types, it by no means tells the entire story of osteocalcin. If anything, a hallmark of this hormone is that it regulates a large and continually growing number of physiological functions and developmental processes 14 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Explaining in part their changes in fat mass, energy expenditure is significantly decreased in Osteocalcin deficient and increased in Esp osb −/− mice (Lee et al, 2007). These observations have ben recently extended to human pancreatic islets, in which the addition of uncarboxylated osteocalcin increases the expression of the Insulin and of Cyclind2 and Cdk4 genes, two genes needed for β-cell proliferation (Sabek et al, 2015). Moreover, circulating osteocalcin levels are inversely correlated in adults with fasting glucose circulating insulin levels, body mass index and body fat (Fernandez-Real et al, 2009).…”
Section: The Anticipated Functions Of Osteocalcinmentioning
confidence: 98%